Seasonal allergic rhinitis – treatment according to 2017 updated guidelines - Pawliczak, Rafał (Lekarz POZ, 2018)
Since the last guidelines regarding allergic rhinitis treatment were published, several new areas of treatment and new drugs have been introduced and more new questions have arisen. Some of them were asked by clinicians and some by researchers. To address the questions properly, a GRADE approach and systematic review of clinical trials and observational studies were needed. Therefore, a group of experts led by Mark S. Dykewicz performed the aforementioned tasks and published new updated guidelines in “Annals of Allergy, Asthma, & Immunology” (2017; 119: 489-511). In this short review we have summarised their important findings, mostly related to allergic rhinitis treatment choice with a focus on montelukast nasal steroids used alone or in combination with intranasal or oral antihistamines. Some of the questions and findings were also put in the local Polish perspective.